BUDAYA KOMUNIKASI POLITIK EKSEKUTIF DAN LEGISLATIF DI KABUPATEN KONAWE SELATAN - Dasmin; Asriani; La Ode Efrianto (Halu Oleo University, 2025)
This research explores how individual entrepreneurs' personalities can be mapped. This study focuses on the culture and political communication of the legislative and executive in realising good governance in South Konawe Regency. The purpose of this study is to describe and analyse the culture of executive and legislative communication in realising good governance in South Konawe Regency. This study uses a qualitative approach by articulating the theory and concept of political communication that is oriented towards transactional communication between the legislative and executive. So, with this perspective, it is important to see how the communication culture occurs between the two regional institutions by using the political communication theory of McNair (2018). The results of the study reveal that the communication culture that exists between the executive and legislative is political communication that upholds family values.